La mobilisation autour des « atrocités de l'ennemi », Russie 1914-1918 - Alexandre Sumpf (Les Cahiers de Framespa)
In Russia, on April 9th, 1915, the tsarist government asked senator A.N. Krivtsov to organize an Extraordinary Inquiry Commission in order to "investigate cases of violation by the German and Austro-Hungarian (and later Turkish) enemies of the laws and customs of war". Its works propagated in Russia and worldwide found their place in an intense mobilization effort driven by the authorities and the civil society, who aimed to present widely the "horrors of war". However, their goal seemed not so much proving the moral superiority of the "just" Russian warfare, than to obtain repeated involvement from civilians and feed the soldiers’ fears. The Krivtsov Commission played a minor role in this affair: its members were not able to define the national perception of the ongoing conflict, to mobilize efficiently the Russian population, to persuade other nations to join the Entente, or even to elaborate a clear inculpation for a grand postwar trial against the German warfare. Indeed, the Krivtsov Commission suffered from its non-professional approach of the propaganda as from its low recognition by officials. The experiment brutally ended in June 1918, when still stood the question of inter-ethnic and inter-class violence highlighted in many reports. Moreover, the Commission’s "liquidation" by the Bolsheviks did not help the memory of the Great War to be properly elaborated.